2021
DOI: 10.17718/tojde.1002803
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Families of Children With Special Needs: Experts’ Opinions

Abstract: Telehealth interventions (TI) are broadly defined as the use of information and communication technologies to deliver information, diagnosis, or educational services. While the use of TI was previously just a choice to support children with special needs and their families, they have become a necessity nowadays when performing face-to-face education and training practices are almost impossible. The current qualitative study aims at describing the opinions and recommendations of the experts toward the basic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Remote training and coaching have the potential to provide PD that is efficient in terms of time, cost, and resources. Experts who are experienced with remote BST and coaching indicated the importance of some components (e.g., incorrect video examples) for successful practices [40]. In this study, the researchers used PowerPoint presentations, correct and incorrect video examples in instruction and modeling steps of BST respectively.…”
Section: Teacher Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote training and coaching have the potential to provide PD that is efficient in terms of time, cost, and resources. Experts who are experienced with remote BST and coaching indicated the importance of some components (e.g., incorrect video examples) for successful practices [40]. In this study, the researchers used PowerPoint presentations, correct and incorrect video examples in instruction and modeling steps of BST respectively.…”
Section: Teacher Outcomesmentioning
confidence: 99%
“…Previous research revealed that PD trainings performed onsite or remotely showed no differences in terms of effectiveness [17; 49] time and associated costs, as well as allowing for more flexible time for scheduling [27; 49]. Additionally, the necessity of and demand for remote training have increased due to COVID-19 pandemic [40].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the studies conducted in Turkey, Kara (2023) investigated the views of parents of children with special needs on digital games. The study was conducted with the parents of 5th grade children who were diagnosed with attention deficit and hyperactivity deficit, learning disability and mild intellectual disability.…”
mentioning
confidence: 99%